2011
DOI: 10.1093/eurjhf/hfq225
|View full text |Cite
|
Sign up to set email alerts
|

Isolated left ventricular non‐compaction in adults: clinical and echocardiographic features in 105 patients. Results from a French registry

Abstract: AimsThe clinical features, prognosis, and even definition of left ventricular non-compaction (LVNC) are still the subject of much debate. The aim of this registry was to describe the clinical, echocardiographic, and prognostic features of LVNC in France. The main endpoint was to assess clinical and echocardiographic predictors of adverse outcome, defined as death or heart transplantation. Methods and resultsBetween 2004 and 2006, 154 suspected cases of LNVC were identified from a nationwide survey in France. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
113
1
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 26 publications
15
113
1
20
Order By: Relevance
“…However, it is still unclear whether increased trabeculation is a result of distinct cardiomyopathy or rather a sign of the remodelling of the failing heart [16][17][18][19]. Previous studies reported that a relatively high percentage of patients with idiopathic heart failure meet criteria for noncompaction [11,20]. In accordance with these studies, we found that more than half of our population had an abnormal amount of trabeculation.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is still unclear whether increased trabeculation is a result of distinct cardiomyopathy or rather a sign of the remodelling of the failing heart [16][17][18][19]. Previous studies reported that a relatively high percentage of patients with idiopathic heart failure meet criteria for noncompaction [11,20]. In accordance with these studies, we found that more than half of our population had an abnormal amount of trabeculation.…”
Section: Discussionsupporting
confidence: 88%
“…Pode apresentar-se com manifestações de IC por disfunção sistólica e/ou diastólica, ou com arritmias cardíacas ou ainda com fenômenos tromboembólicos. O ecocardiograma e a ressonância magnética do coração são os exames complementares de escolha no diagnóstico 285,286 . Não existem estudos específicos no tratamento da IC nesse grupo de pacientes.…”
Section: Miocardite (Tabela 35)unclassified
“…[5][6][7][8][9][10][11][12][13][14][15] Typical complications include congestive heart failure, ventricular arrhythmias and thromboembolic events. [12][13][14]16,17 Recently, the association of LVNC with metabolic diseases, genetic syndromes and other cardiac abnormalities has been reported. [18][19][20] Genetic studies have shown sarcomere gene mutations in some patients with isolated LVNC similar to those with dilated or hypertrophic cardiomyopathy, and a recent study has found similar mutations in patients with Ebstein anomaly.…”
Section: Since Its First Description Left Ventricular Non-compactionmentioning
confidence: 99%